Foot exercise plus education versus wait and see for the treatment of plantar heel pain (FEET trial): a protocol for a feasibility study - Franettovich Smith, Melinda M. (J Foot Ankle Res, 2020)
BACKGROUND: Plantar heel pain (PHP) is present in a wide range of individuals and creates significant burden to quality of life and participation in physical activity. The high recurrence rates and persistence of PHP suggests current management options may not address all potentially modifiable factors associated with the condition. Reports of intrinsic foot muscle (IFM) atrophy in individuals with PHP, together with biomechanical evidence of their important contribution to optimal foot function, suggests that an intervention focused on IFM training may be beneficial in managing PHP. We will test the feasibility of a prospective, assessor-blinded, parallel-group, randomised clinical trial that compares foot exercise plus education to brief advice in individuals with PHP. METHODS: Twenty participants with PHP will be randomly allocated to one of two groups for a 12-week intervention period: (i) foot exercise plus education, or (ii) brief advice. The foot exercise plus education group will attend eight sessions with a physiotherapist and receive detailed education on self-management strategies as well as a progressive exercise program for the IFMs. The brief advice group will attend one session with a physiotherapist and receive brief information about self-management strategies and reassurance. Outcome measures will be obtained at baseline and the primary end-point of 12 weeks. Primary outcomes will be the feasibility of conducting a full-scale randomised clinical trial (RCT), and the credibility and acceptability of the foot exercise plus education intervention. Secondary outcomes will explore treatment effects, which will consist of pain, physical function, physical activity level, pain self-efficacy, perceived treatment effect, magnetic resonance and ultrasound image measurement of IFM morphology, ultrasound imaging measurement of plantar fascia thickness, IFM motor performance, foot posture, foot mobility, ankle dorsiflexion range of motion, toe flexor and plantar flexor strength/endurance. DISCUSSION: To reduce the burden of PHP on individuals and society, there is a need to establish effective treatments that are feasible and accepted by patients and health professionals. This trial will be the first to evaluate the feasibility of conducting a full-scale RCT, as well as the credibility, acceptability, and treatment effects, of education and foot exercise for PHP. The findings of this study will inform the development of a full-scale RCT. TRIAL REGISTRATION: The trial protocol was prospectively registered with the Australia and New Zealand Clinical Trial Registry (ACTRN12619000987167) on 11th July 2019.